Respuesta :
Step-by-step explanation:
Given
- 5x + 3 = 2x - 1
or, 2x + 5x = 3 + 1
or, 6x = 4
or, x = 4/ 6
Therefore x = 2 /3
Hope it will help :)❤
Step-by-step explanation:
Subtract
3
3
3
from both sides of the equation
−
5
+
3
=
2
+
1
−
5
+
3
−
3
=
2
+
1
−
3
2
Simplify
Subtract the numbers
Subtract the numbers
−
5
=
2
−
2
3
Subtract
2
2x
2x
from both sides of the equation
−
5
=
2
−
2
−
5
−
2
=
2
−
2
−
2
4
Simplify
Combine like terms
Combine like terms
−
7
=
−
2
5
Divide both sides of the equation by the same term
−
7
=
−
2
−
7
−
7
=
−
2
−
7
6
Simplify
Cancel terms that are in both the numerator and denominator
Divide the numbers
=
2
7